Tackling air pollution in dense urban areas The case of Santiago, Chile - Tikoudis, Ioannis (OECD Publishing, 2022)
Reducing air pollution is a major policy challenge, especially in densely populated urban areas where human exposure to emissions is considerable. This paper develops and examines a series of scenarios for the evolution of transport-related emissions in the area of Santiago, Chile. The analysis suggests that ramping up efforts to electrify the bus fleet may eliminate 25% of the CO2 and at least 10% of the remaining air pollutant emissions in 2050. These figures increase to 45% and 30%, respectively, if rapid electrification is accompanied by tax schemes. The paper highlights the potential synergies of policies curbing climate change and tacking air pollution from the viewpoint of urban transport
Keywords: Environment; Chile